The Relation Between the Refractive Index of the Equatorial Ionospheric F2 Region and Long-Term Solar Indices - Sagir, Selcuk; Yesil, Ali (Springer, 2018)
Ionospheric refractive index is especially important in the reflection and propagation of HF (3-30 MHz) waves from the ionosphere. For this reason, in this study, the relation between the real parts (mu(2)(0), mu(2)(x) and mu(2)(p)) of the refractive index computed as based on the direction of the Earth's magnetic field for 300 km altitude in the equatorial ionospheric F2 region and the long-term solar indices (Sunspot Number-R12, Solar Flux at 10.7 cm -F10.7, Coronal Mass Ejection-CME) has been examined by using the multiple regression model. As a result of the examinations, it has been determined that there is a very strong relation between the three refractive index values and solar indices. While it was determined that the R12 and F10.7 indices have a very strong relation, it was also determined that CME did not have a statistically significant relation. This insignificant situation may only be explained with the magnetic field of the Earth acting like a shield.
Keywords: Ionosphere; Refractive index; Long-term solar parameters; Multiple regression model